THE KINEMATICS OF REGULAR STRUCTURES - Anisimova, G. B. (Одеські астрономічні публікації, 2013)
Three kinds of movements, providing stability of Universal Sky Net (USN), are listed. The series of peculiar kinematical parameters, connected with the USN structure are also given.